2012
DOI: 10.3389/fonc.2011.00057
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 is a Promising Therapeutic Target in Breast Cancer

Abstract: Breast cancer is the most common type of cancer among American women, and remains the second leading cause of cancer-related death for female in the United States. It has been known that several signaling pathways and various factors play critical roles in the development and progression of breast cancer, such as estrogen receptor, Notch, PTEN, human epidermal growth factor receptor 2, PI3K/Akt, BRCA1, and BRCA2. Emerging evidence has shown that the F-box protein S-phase kinase associated protein 2 (Skp2) also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 114 publications
(223 reference statements)
0
63
0
Order By: Relevance
“…27, 30, 31 Skp2 expression has been considered as a biomarker of poor prognosis for breast cancer, melanoma, and nasopharyngeal carcinoma. 32, 54, 55 Interestingly, a recent study revealed a possible role for Skp2 in maintaining the CSC-like phenotype of nasopharyngeal carcinoma cells. 56 Because of its oncogenic activity and its role in cancer development, Skp2 has been suggested as a novel and attractive therapeutic target for the cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…27, 30, 31 Skp2 expression has been considered as a biomarker of poor prognosis for breast cancer, melanoma, and nasopharyngeal carcinoma. 32, 54, 55 Interestingly, a recent study revealed a possible role for Skp2 in maintaining the CSC-like phenotype of nasopharyngeal carcinoma cells. 56 Because of its oncogenic activity and its role in cancer development, Skp2 has been suggested as a novel and attractive therapeutic target for the cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Skp2 is an E3 ligase involved in cell-cycle progression by targeting various cell-cycle regulators, including p27, p21, and FOXO1, for degradation. Skp2 is overexpressed in a variety of human cancers including cancers of the breast, colon, and prostate, as well as lymphoma and melanoma [65]. In A549 nonsmall lung carcinoma cells, lycopene-derived metabolites, such as apo-10′-lycopenic acid, can induce cell-cycle arrest at the G 1 /S, transition.…”
Section: Potential Mechanisms Of Actions Of Lycopenementioning
confidence: 99%
“…Numerous studies to date have provided evidence showing the oncogenic potential of SKP2, and its cross-talk with multiple signaling pathways involved in carcinogenesis such as PI3K/AKT, mTOR, ERK, NF k B, Ras/MAPK, and IGF (Wang et al, 2012c). Overexpression of SKP2 can drive quiescent cells to enter the cell cycle (Sutterluty et al, 1999), and promote adhesion-independent growth of cancer cells (Carrano and Pagano, 2001; Signoretti et al, 2002).…”
Section: Skp2mentioning
confidence: 99%